2008
DOI: 10.1108/13563280810848210
|View full text |Cite
|
Sign up to set email alerts
|

Communicating to a diverse workforce

Abstract: Purpose -This paper aims to determine whether language proficiency, race and education levels influence employees' perceptions of symbolic corporate identity elements of Lonmin Platinum, a mining company operating in the development context of South Africa. Design/methodology/approach -The nature of the endorsed symbolic corporate identity was determined by means of personal observations and semi-structured interviews with managers. To determine employees' perceptions a quantitative questionnaire survey was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…In general, the disclosure of SR information, and therefore also environmental information, is part of the branding of corporate identity, an aspect of its behaviour that distinguishes one firm from another and strategically differentiates it from the competition (Marwick and Fill, 1997; Gray and Balmer, 1998; Olutayo Otubanjo and Melewar, 2007; Holtzhausen and Fourie, 2008; Bewley and Li, 2000; Patenaude, 2011; Mobus, 2012). In this sense, environmental responsibilities are factors that govern the formation of opinions about a firm's reputation (Capriotti and Moreno, 2007).…”
Section: Market Orientation From the Sr Perspective: An Environmentalmentioning
confidence: 99%
“…In general, the disclosure of SR information, and therefore also environmental information, is part of the branding of corporate identity, an aspect of its behaviour that distinguishes one firm from another and strategically differentiates it from the competition (Marwick and Fill, 1997; Gray and Balmer, 1998; Olutayo Otubanjo and Melewar, 2007; Holtzhausen and Fourie, 2008; Bewley and Li, 2000; Patenaude, 2011; Mobus, 2012). In this sense, environmental responsibilities are factors that govern the formation of opinions about a firm's reputation (Capriotti and Moreno, 2007).…”
Section: Market Orientation From the Sr Perspective: An Environmentalmentioning
confidence: 99%
“…Positive corporate image makes an organization attractive to the public (both customers and employees) (Vuokko, 2002). Holtzhausen and fourie (2008) highlight that organizations benefit from being perceived positively by employees and customers. A solid corporate image can be attractive to its constituencies and they have certain perceptions about an organization before they even begin to interact (Argenti, 1998).…”
Section: Hci and Performancementioning
confidence: 99%
“…The official language policy explores how top-down management and bottom-up perspectives correlate (Kingsley, 2013) Language proficiency, race, and educational levels have an impact on how the employee identifies himself with the organization. Holtzhausen and Fourie (2008), in a study conducted in a mining company in South Africa, found that although race and educational level did not create much difference in forming a corporate identity; the employee's English proficiency made a marked difference. This implies that managers should be aware of what language they choose when communication leads to information dissemination.…”
Section: Literature Reviewmentioning
confidence: 99%